Improving the performance of anaerobic bacteriology in a hospital laboratory. - Morgan, J R (1977)
A comparison was made of the performance of a newly established anaerobic section of a clinical laboratory and the routine diagnostic section in terms of isolation and identification of anaerobic bacteria. Both sections attempted to isolate obligate anaerobes from the same clinical specimens which were not transported in anaerobic containers. Anaerobic and diagnostic sections isolated anaerobes from 35% and 6% respectively of clinical specimens. The use of antibiograms greatly improved the identification of anaerobic organisms.